VD_FINDINFO HC / 2015 / 383 vom 1. Mai 2015 - VD Tribunal cantonal (2015)
DROIT D'ÊTRE ENTENDU, DÉCISION D'IRRECEVABILITÉ, RETARD INJUSTIFIÉ, CONCLUSIONS | 29 al. 1 Cst., 29 Cst., 319 CPC (CH), 319 let. c CPC (CH)